ANALYSIS OF CONSUMERS' GREEN PURCHASE BEHAVIOR ON BOTTLED WATER THROUGH A GREEN BRAND IMAGE APPROACH - Budi Setiawan; Gen Gen Gendalasari; Dewi Raisa Putrie (Kesatuan Press, 2022)
This study analyzes the effect of greenwash on consumer green purchasing behavior by a company mediated by the role of a company's green brand image. This study was conducted on consumers who know about bottled drinking water product brands in Indonesia. Primary data was performed using a questionnaire with a total of 385 data. The data in this study is quantitative. This study uses Structural Equation Modeling (SEM). The software used in this study is LISREL 8.8 and SPSS 22. The results of this study are that greenwashing has a negative effect on the brand image of green companies, and green brand image has a positive effect on green consumer purchases. Green brand image has an essential role in mediating the effect of greenwashing on green consumer purchase behavior. Therefore, companies need to reduce greenwashing activities and enhance their green brand image to increase green consumer purchase behavior.